Community Outreach Gaps in Drafting Regional Regulations: A Call for Enhanced Government Socialization - Budianto, Kun; Badarudin Azarkasyi (Universitas Islam Negeri Raden Fatah Palembang, 2024)
The enactment of Law Number 12 of 2011 concerning drafting laws and regulations constitutes a crucial foundation for legislative and regulatory development. This was accepted by the community because many Regional Regulations of The Leader (Regional Reg. of The Leader/Perkada) were revised and even revoked by the government. This study aims to inform the formulation of the Regional Medium Term Development Plan in Lahat. Its objective is to evaluate the alignment of legal developments with Law Number 12 of 2011. The form of research is analytical descriptive, namely research that does more than just describe a problem. Data collection involves a prescriptive legal method, focusing on researching legal aspects. The study reveals that during the preparation of the Lahat Regional Medium Term Development Plan (RPJMD) for 2019-2023 it was approved by Lahat Regional People's Representative Assembly /DPRD for the enactment of Regional Regulation Number 2 of 2019 concerning the Regional Medium-Term Development Plan (RPJMD) in the framework of revising Law Number 12 of 2011 concerning the formation of adequate laws and regulations, namely regional government laws and regulations, in this case the Regent's proposal has been stipulated by Lahat Regional People's Representative Assembly/DPR. This revision aims to ensure compliance with regional government laws and regulations. However, there remains a significant gap in community socialization efforts.